3s-1=2s-10

Simple and best practice solution for 3s-1=2s-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3s-1=2s-10 equation:


Simplifying
3s + -1 = 2s + -10

Reorder the terms:
-1 + 3s = 2s + -10

Reorder the terms:
-1 + 3s = -10 + 2s

Solving
-1 + 3s = -10 + 2s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-2s' to each side of the equation.
-1 + 3s + -2s = -10 + 2s + -2s

Combine like terms: 3s + -2s = 1s
-1 + 1s = -10 + 2s + -2s

Combine like terms: 2s + -2s = 0
-1 + 1s = -10 + 0
-1 + 1s = -10

Add '1' to each side of the equation.
-1 + 1 + 1s = -10 + 1

Combine like terms: -1 + 1 = 0
0 + 1s = -10 + 1
1s = -10 + 1

Combine like terms: -10 + 1 = -9
1s = -9

Divide each side by '1'.
s = -9

Simplifying
s = -9

See similar equations:

| -7r+6r=-16 | | 3x+37=12-62 | | -9m=-8m-4 | | -7r+6t=-16 | | 11+18b=19b | | 9=0.5(-9.81)(x^2) | | -9y+5=-7-7y | | -5v-4=-7v | | 53a-55=42 | | -(q+10)=-20 | | =x^2+20x-19 | | 10p-18p+-14=18 | | -30=-2(3c-7) | | x+x-30=2x | | -9-6q=6-9q | | 2w+9ifw=15 | | 3v-12=4v | | 8(1r-12d)= | | -19+3g=5g+17 | | d/3−6=19 | | 5q+7=34 | | 10-14j=-12j | | 3g+-7=8 | | -1y^2-3=-y^2-y-3 | | -4(k-17)=0 | | 0.08x+0.11(3x+37000)=18290 | | 12d+6=9d | | -9-4K=-1-5k | | 1x/2x-1/10x=1/5-1/4 | | 4p=6p-16 | | -3(m-12)=-12 | | 81*.15= |

Equations solver categories